Unveiling NiOx /Perovskite Interfaces: Charge Transport and Device Performance in Perovskite Solar Cells - Lee, Hanseul; Jung, Hye Ri; Pak, Sooyeon; Kwon, Namhee; Kim, Sang Hoon; Na, Junhong; Ko, Seoyeon; Yoon, Seokhyun; Kim, Won Mok; Jeong, Jeung-hyun; Kim, Donghwan; Park, Soohyung; et al. (American Chemical Society, 2025)
NiO x is a p-type semiconductor widely used as a hole transport material in perovskite solar cells (PSCs), yet the impact of fabrication methods on its interfacial properties and the underlying mechanisms remains unclear. This study investigates how the fabrication process-nanoparticle precursor (NP NiO x ) and sputtering deposition (SP NiO x )-and interfacial space charge effects influence charge transport and device performance in NiO x /perovskite systems. SP NiO x exhibits a higher Ni3+/Ni2+ ratio and greater conductivity but induces significant hole depletion and band bending at the interface, leading to reduced open-circuit voltage and efficiency. In contrast, NP NiO x shows weaker hole depletion and a negligible hole barrier and enhances hole extraction, achieving a higher efficiency. The improved interfacial behavior of NP NiO x is attributed to the presence of carbon ligands, which mitigate interfacial recombination. These findings highlight the critical role of interfacial engineering in optimizing charge transport and performance in PSCs, providing valuable insights into the design of efficient hole transport layers (HTLs).